Marketing analysis: Security and public trust online shopping at Tokopedia.co.id - Yaskun, Mohammad; Syairozi, Muhammad Imam; Safa’atillah, Nurus; Efendi, Yuhronur; Taufik, Mohammad (Proceeding of International Management Conference and Progressive Papers, 2023)
The changes in behavior patterns and consumer needs due to the development of technology and information flow makes more practical behavior which means consumers need speed and accuracy in meeting their needs. This led to the ever[1]changing e-commerce model developed with more modern packaging of technology and information. People in general mention that e-commerce is the answer to the speed and accuracy of fulfillment of needs where e-commerce offers one of its competitive advantages is removing the concept of space and time. The purpose of this study is to know and analyze the influence of privacy, security, and trust on the intention of shopping online in Tokopedia.co.id both partial and simultaneous and know and analyze which independent variables have the dominant effect on the intention of shopping online in Tokopedia.co.id. The type of research used in this study is explanatory research with survey method and the number of samples in this study as many as 220 respondents. The sampling technique is obtained using accidental sampling method. The data source uses primary data and secondary data i.e. literature and updated data from the internet. While the data analysis technique used the quantitative analysis using analysis through SPSS software, by Linear Regression Analysis. From the results of the study by multiple linear regression analysis using F-test, it can be concluded that privacy variables, to security, and trust has a simultaneous influence on the variable intention of shopping, then the results of the analysis of t-test can be concluded variable of privacy, security, and trust partially significant effect on the variable intention of shopping, and based on the results of the coefficient of regression, it can be found the variables that have a dominant effect on the intention of shopping online in the Tokopedia.co.id is a security variable